2017
DOI: 10.2174/1874364101711010262
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Versus Accelerated Collagen Cross-Linking for Keratoconus: A Comparison of Visual, Refractive, Topographic and Biomechanical Outcomes

Abstract: Objective:The aim was to compare the visual, refractive, topographic and biomechanical outcomes in patients with progressive keratoconus treated with either conventional or accelerated crosslinking at one year follow up.Methods:It is a prospective, non-randomised interventional study of 76 patients who underwent conventional (CXL; 3mW/cm2 for 30 minutes) or accelerated cross linking (KXL; 30mW/cm2 for 4 minutes) for progressive keratoconus. Baseline and postoperative visual acuity, manifest refraction, corneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…However, other studies have demonstrated that both procedures have a comparable effect in stabilizing keratometry. 51,52 It is of note that typically both SCXL and ACXL are generally preceded with epithelial removal (epithelium-off CXL), although investigations have been conducted to explore the potential influence on clinical outcomes between epithelium-off and transepithelial (epithelium-on) procedures using both SXCL and ACXL protocols. 53,54 In an attempt to try to clarify the potential benefits of CXL, we undertook this current meta-analysis to compare the effectiveness and safety of ACXL in comparison to SCXL.…”
mentioning
confidence: 99%
“…However, other studies have demonstrated that both procedures have a comparable effect in stabilizing keratometry. 51,52 It is of note that typically both SCXL and ACXL are generally preceded with epithelial removal (epithelium-off CXL), although investigations have been conducted to explore the potential influence on clinical outcomes between epithelium-off and transepithelial (epithelium-on) procedures using both SXCL and ACXL protocols. 53,54 In an attempt to try to clarify the potential benefits of CXL, we undertook this current meta-analysis to compare the effectiveness and safety of ACXL in comparison to SCXL.…”
mentioning
confidence: 99%
“…The decrease in CCT is an indirect marker of efficacy of AXL, confirming compactness of collagen fibrils, apoptosis of stromal keratocytes and improved biomechanical stability 8,9,15 . Hashemi et al 8,9 identified a statistically significant decrease in CCT at 18 months following AXL with 18 mWatt/cm 2 for 5minutes.…”
Section: Discussionmentioning
confidence: 75%
“…In a comparison study between conventional and accelerated CXL, both groups showed a significant decrease in CCT and Thin at 1 month, but the maximum decrease was shown in the accelerated CXL group at 3 months and the increase in corneal thickness was slower during postoperative period in that group. 31 In another study, Razmjoo et al compared these two CXL methods and showed that the Thin was further reduced by accelerated CXL. 32 The use of high ultraviolet intensity may be another reason for the decrease in CCT, Thin and CV seen in our study.…”
Section: Discussionmentioning
confidence: 99%